Health Gymnastics - Dehkanova Mahmuda Artikovna (Zien Journals, 2022)
One of the most common and easy means to maintain our health is health-improving gymnastics, which is distinguished by a variety of exercises and the possibility of a wide healing effect on the person who practices it.
Keywords: gymnastics; recreational gymnastics; gymnastics and health; human health